The Actual U.S. Unemployment Rate Was 24.4% in May 2020 - John Komlos (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The official U.S. unemployment rate is an inadequate measure of actual labor market conditions. This poses a major challenge for researchers and confuses both the public and policy makers. A new definition of unemployment is proposed. It considers those part-time workers who would like to work full time as 62.7% employed and 37.3% unemployed, inasmuch as this is the proportion of time they worked relative to full-time workers prior to the pandemic. In addition, in contrast to the BLS, we consider those workers who are wanting to work but have not searched for work within the prior month as being unemployed. We find that the actual unemployment rate in May 2020 was 24.4% or 183% of the headline rate of 13.3%.
Keywords: B40; C82; J40; J49; J69; 330; covid-19; pandemic; unemployment rate; labor market slack; discouraged workers; involuntary part-time workers